2020
DOI: 10.29252/jcmh.6.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Two Methods of Aquatic Exercise and Vitamin D Supplementation on Stereotypic Behaviors and BMI in Children with Autism Spectrum Disorder

Abstract: Background and Purpose: Autism spectrum disorder (ASD) is a neurodevelopmental disorder that occurs in early childhood. There are various methods for training and rehabilitation of this disorder. So, the aim of the present study was to compare the effect of aquatic exercise and vitamin D supplementation on stereotypic behaviors and body mass index (BMI) in boys with ASD. Method: The present experimental study was conducted using a pretest-posttest design with random groups. Thus, 40 children with ASD (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Two studies were included in the overall interpretation but not included in the meta-analysis due to the use of an assessment tool not used by the others 18,19 . The reasons for excluding the 14 full texts were as follows: 8 did not answer our systematic review question [20][21][22][23][24][25][26][27] , 1 was retracted by the journal due to incorrect data 28 , 2 were case reports 29,30 and 3 were open-label trials [31][32][33] . The screening and selection of the studies are presented in the PRISMA flowchart shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Two studies were included in the overall interpretation but not included in the meta-analysis due to the use of an assessment tool not used by the others 18,19 . The reasons for excluding the 14 full texts were as follows: 8 did not answer our systematic review question [20][21][22][23][24][25][26][27] , 1 was retracted by the journal due to incorrect data 28 , 2 were case reports 29,30 and 3 were open-label trials [31][32][33] . The screening and selection of the studies are presented in the PRISMA flowchart shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%